Public Perception And Understanding Of Profit Sharing In Islamic Banks (Case Study In Karangtalun Village, Kalidawir Subdistrict, Tulungagung Regency) - Elwi Yuda Laksana; Eka Wahyu Hestya Budianto (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2025)
This study aims to understand the perceptions and understanding of the people in Karangtalun Village regarding the profit-sharing concept in Islamic Banks. This research uses a qualitative approach, collecting data from the community in Karangtalun Village. Data collection methods include observation, interviews, and documentation. The data analysis method consists of three main stages: data reduction, data presentation, and conclusion drawing. Most people in Karangtalun Village have a negative perception of profit-sharing, with doubts about its validity, viewing it similarly to interest; only a few individuals, such as academics and religious figures, hold a positive view of profit-sharing in Islamic banks. Similarly, the community’s understanding is still limited; most people do not fully grasp the concept of profit-sharing or its mechanism in detail, with many still believing that profit-sharing is the same as interest. In contrast, academics and religious leaders tend to have a better understanding of Islamic bank profit- sharing. The negative perception and lack of understanding of profit-sharing are due to several factors, such as the lack of experience with profit-sharing, individual backgrounds, and unclear information. These factors contribute to the community’s less favorable perception and understanding of profit- sharing.